Cheating under the Circumstances in Marital Relationships: The Development and Examination of the Propensity towards Infidelity Scale - Carmen Gabriela Lișman; Andrei Corneliu Holman (Social Sciences, 2021)
Most of the previously developed scales addressing infidelity were developed on young samples in dating relationships and with limited couple experience. The present study proposes an instrument to measure the proneness for infidelity among married people with substantial experience as a couple. Specific contexts described by the items, in which unfaithful behavior might occur, were selected from those revealed by previous research on people’s motives of past infidelity. Across two studies (N = 618) we examined the factorial structure and the psychometric characteristics of the Propensity towards Infidelity Scale (PTIS). Results revealed a one-dimensional structure of the PTIS and supported its reliability, its construct, criterion and incremental validity. PTIS emerged as negatively associated with two measures of adherence to moral standards, and positively related to past unfaithful behavior. Furthermore, the new instrument was found to bring a significant contribution in explaining these behaviors beyond two other scales of infidelity intentions.